Meningkatkan kemampuan pemahaman siswa dalam materi himpunan melalui model pembelajaran make a match - Panut Panut; Zuli Nuraeni; Ricki Yuliardi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
The purpose of this study is to determine the application of make a match learning model can improve students' understanding in the material set.This research is a Classroom Action Research (CAR). The subjects of this study were the students of class VII A SMPN 2 Kalimanggis District Kuningan academic year 2016/2017. The study was conducted collaboratively between researchers, observers, and subjects studied. Implementation of this research is done in the even semester of the academic year 2016/2017. This classroom action research process is conducted in two cycles, each cycle consists of four main actions: planning, action implementation, observation, and reflection. The end of each cycle is tested using question instrument. The test used is a description test performed at the end of cycle I and cycle II. Besides as an evaluation tool, this test is conducted to know the students' understanding. Data processing techniques student learning outcomes are performing tests, collecting test results, correcting test results, scoring the acquisition of test results, determining the value of test results and determining the average value.The results showed that the average value of learning outcomes in the first cycle to get the value of 75 and the second cycle of the average value of learning outcomes increased to obtain the value 87. Similarly, the results of student activity observations showed an increase. In the first cycle of participation and activity of students is 60% and in the second cycle of participation and student activity increased to 80%, so most of the participation and activities of students categorized well. While the results of teacher performance observation obtained the value of implementation aspects of observations in the first cycle of 80% and in the second cycle managed 100%. This study concludes that make a match learning model can improve students' comprehension ability in Mathematics subject in the material set.